2023
DOI: 10.3389/fcvm.2023.1162205
|View full text |Cite
|
Sign up to set email alerts
|

Phospholamban R14del disease: The past, the present and the future

Abstract: Arrhythmogenic cardiomyopathy affects significant number of patients worldwide and is characterized by life-threatening ventricular arrhythmias and sudden cardiac death. Mutations in multiple genes with diverse functions have been reported to date including phospholamban (PLN), a key regulator of sarcoplasmic reticulum (SR) Ca2+ homeostasis and cardiac contractility. The PLN-R14del variant in specific is recognized as the cause in an increasing number of patients worldwide, and extensive investigations have en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 101 publications
0
10
0
Order By: Relevance
“…Additional studies in iPSC-CMs indicated the beneficial effects of the small molecule activator BiX (BiP [binding immunoglobulin protein] inducer X) to stimulate UPR, the Ca 2+ sensor GCaMP6f or the Ca 2+ -binding protein parvalbumin, and the PLN double-mutant (L31A/I40A), which enhanced Ca 2+ transport. 19,23 However, a recent study reported a decrease in transient Ca 2+ amplitude in association with accelerated intracellular Ca 2+ dynamics in iPSC-CMs derived from 1 patient with this mutation. 21 Further studies are needed to explain these intriguing findings that are in sharp contrast with previous results.…”
Section: Surprises and Prospectsmentioning
confidence: 96%
See 3 more Smart Citations
“…Additional studies in iPSC-CMs indicated the beneficial effects of the small molecule activator BiX (BiP [binding immunoglobulin protein] inducer X) to stimulate UPR, the Ca 2+ sensor GCaMP6f or the Ca 2+ -binding protein parvalbumin, and the PLN double-mutant (L31A/I40A), which enhanced Ca 2+ transport. 19,23 However, a recent study reported a decrease in transient Ca 2+ amplitude in association with accelerated intracellular Ca 2+ dynamics in iPSC-CMs derived from 1 patient with this mutation. 21 Further studies are needed to explain these intriguing findings that are in sharp contrast with previous results.…”
Section: Surprises and Prospectsmentioning
confidence: 96%
“…18 Several PLN variants, associated with phospholambanopathies, exhibiting dilated cardiomyopathy or arrhythmogenic cardiomyopathy, have been found and include Arg9Cys, Arg9His, Arg25Cys, Leu39Ter, Glu2Ter, and Arg14del (Figure 1) and 2 promoter ones (−36 A>C and −42 C>G). 19 The homozygous Leu39stop was associated with a lack of PLN expression and pointed to distinct differences associated with PLN ablation between humans and mice.…”
Section: Surprises and Prospectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular interest is PLN-R14del, the most prevalent cardiomyopathy-related mutation in the Netherlands, linked to the development of dilated and arrhythmogenic cardiomyopathies. 4 While not achieving full consensus, this mutation has been suggested to have a superinhibitory effect on SERCA2a activity due to its enhanced binding affinity for the pump. The resulting reduction of the SR Ca 2+ content and elevation of diastolic Ca 2+ have been indicated as potential contributors to the contractile impairment, diastolic dysfunction, and arrhythmogenesis observed in patients carrying this mutation.…”
Section: Article See P 252mentioning
confidence: 99%